Isra'iliyyat dalam Tafsir Modern: Studi Tentang Turunnya Adam dari Surga - Mufida, Luluk Inda Rini; Mubarok, Ghozi (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2020)
The narration of isrā’īlīyāt in the Qur’anic exegesis has been an object of criticism in modern times. However, the modern Qur’anic exegesis are not entirely free from the isrā’īlīyāt. This article seeks to examine the distribution of the isrā’īlīyāt in the writings of modern Qur’anic exegesis and their attitude towards it. By explicating the story of Adam’s falling from the heaven, it attempts to delve into four modern Qur’anic exegeses, namely Rashīd Riḍā, Hamka, M. Quraish Shihab, and Thoifur ‘Ali Wafa. This article argues that, first, those Qur’anic exegesis are not uninfected with the isrā’īlīyāt, although the number varies each other. In this case, Tafsīr Firdaws al-Na‘īm and Tafsir Al-Azhar ranks as the highest interpretation used isrā’īlīyāt. Second, the attitude of modern exegetes towards the isrā’īlīyāt is also not singular. Rashīd Riḍā and Buya Hamka tend to approach the isrā’īlīyāt in a critical manner. Quraish Shihab, although still narrating isrā’īlīyāt in his work, he tends to regard it as an insignificant source in the Qur’anic exegesis. While Thoifur tends to be loose and accommodating the isrā’īlīyāt.